El rol del estado y la participación de organismos internacionales en la evaluación educativa en Ecuador, periodo 1996-2012. - Castro Alvarez, María Gloria. (2018)
The present investigation analyzes the actions of the State, as well as the participation of the international organisms in the different governmental experiences of educational evaluation carried out in Ecuador, the same ones that took place in two different political moments. A first moment in front of a minimal State proper to a neoliberal regime and a second moment characterized by the reappearance of the State and its main functions: rectoría in sectors considered key, regulation, planning and control. Based on the object of study proposed by this thesis, a qualitative methodological strategy based on secondary sources of bibliographic, documentary and normative information was chosen. Special interest was the compilation of technical reports and results of the different educational evaluation processes that allowed to identify the map of the main decision makers in the field of educational policies of the country in the two periods mentioned; the latter with the intention of capturing the capabilities of the State, its impact on the relationship with international organizations and its impact on educational evaluation programs.